Cardiac troponin I as mortality predictor in acute exacerbation of chronic obstructive pulmonary disease - Gupta, Seema; Saini, Varinder; Kaur, Jasbinder; Jaswal, Shivani; Kaur, Harjeet; Kaur, Sumeet (International Journal of Research in Medical Sciences, 2017)
Background: Comorbidities are important determinants of outcome and quality of life of patients with chronic obstructive pulmonary disease (COPD). The risk of cardiovascular events in COPD patients is three to five-fold high. COPD is often associated with right ventricular hypertrophy and pulmonary hypertension. Various studies have associated levels of cardiac troponin I (cTnI) with severity and duration of acute exacerbation of COPD (AECOPD). The objective of the present study was to assess the usefulness of serum cTnI as mortality predictor in AECOPD patients. Methods: An observational, prospective and non interventional study was conducted in 50 patients with AECOPD admitted in the pulmonary medicine emergency or ward of a tertiary care hospital of Northern India. AECOPD was diagnosed according to Global Initiative for chronic obstructive lung disease guidelines. cTnI levels were estimated within 24 hours of admission by method based on chemiluminiscence along with routine investigations. Levels ≥ 0.01ng/ml were taken as positive. The patients were followed up for 30days for outcome in terms of mortality and morbidity. Data was entered and analyzed by SPSS package and two sided p values<0.05 were considered statistically significant. Results: The serum cTnI was found to be positive in 34% of patients with AECOPD. The in- hospital mortality was significantly low in patients having cTnI <0.01ng/ml as compared to patients with cTnI ≥0.01ng/ml. The patients with cTnI levels ≥0.01ng/ml had significantly higher mean PaCO2 levels and higher requirement for invasive or noninvasive ventilation during hospital stay as compared to patients having cTnI <0.01ng/ml (p=0.04 and 0.016 respectively). Conclusions: Levels of cTnI≥0.01ng/ml may be considered as a biomarker to predict mortality in AECOPD patients.